TGR5 potentiates GLP-1 secretion and cause pancreatic islet regeneration in response to Tithonia diversifolia saponin-rich extract in diabetic model mice - Oluwamodupe Cecilia Ejelonu, PhD (Biochemistry); Olusola Olalekan Elekofehinti; Isaac Gbadura Adanlawo; Rakesh Kundu (Elsevier, 2022)
Background: Activation of Takeda G-protein bile acid receptor 5 (TGR5) secretes glucagon-like peptide-1 (GLP1) downstream insulin release. Saponin which has been indicated as the antidiabetic principle in plant shared similar steroidal scaffold with cholic acid (primary agonist of TGR5), hence antidiabetic mechanism of Tithonia diversifolia leaves saponin-rich extract (TDS) was investigated via TGR5/GLP-1 pathway. Methods: Insulin secretion and expression of GLP1 were measured in MIN6 β-cells incubated with TDS and cholic acid a known agonist of TGR5 at (25, 75, 125, 325) µg/ml and treatment were compared to incubation with insulin secretagogue metformin (50 mM). The action of TDS on TGR5 was studied in vivo using swiss albino mice. Results: β-cell assay showed dose dependent increase in insulin secretion/1 × 106cells incubated with TDS (25, 75, 125, 325 µg/ml) when compared with positive control (50 mM metformin) and vehicle control (Cholic acid). TDS increased GLP-1 and insulin expression and decrease the percentage of%HbA1c in treated mice when compared with control (p < 0.05). TGR5 gene were highly expressed in cell incubated with 20-60 mg/kg body weight of TDS compared to STZ-induced diabetic mice and immunoblotting of TGR5 protein showed higher expression in all groups treated with TDS compared to STZ-induced diabetic mice. Conclusion: TDS exhibit its antidiabetic mechanism via TGR5 agonism leading to increase GLP-1 expression and subsequently insulin release. Hence TDS may represent a new therapeutic strategy for type-2 diabetes, a finding which could be further investigated in clinical trials.